Triple Helix Collaboration in PT. INALUM’s Corporate Social Responsibility Program for Empowering Coastal Women in Kuala Indah Village - Dara Aisyah; Muhammad Sontang; M. Deny Effendy Tambusay (Journal of Environmental and Development Studies, 2026)
This study examines the implementation of Triple Helix collaboration within PT. INALUM’s Corporate Social Responsibility (CSR) program in empowering coastal women engaged in clam shell peeling activities in Kuala Indah Village through the utilization of clam shell waste. The research explores how collaboration among government, industry, and academia can create an innovative and sustainable empowerment ecosystem for coastal communities. The study employs a mixed-methods approach using a case study design integrated with Participatory Action Research (PAR). Quantitative data were collected through surveys involving 100 purposively selected respondents, while qualitative data were obtained from in-depth interviews, field observations, and document analysis. The research process included needs assessment, training on processing clam shell waste into calcium oxide-based products, participatory evaluation, and community mentoring. The findings indicate that the socio-economic conditions of coastal women remain relatively low, characterized by limited educational attainment, unstable daily income averaging IDR 50,000 from middlemen (tauke), and restricted access to empowerment programs. The study further reveals that Triple Helix collaboration contributes to emerging socio-economic transformation through product innovation based on coastal waste processing and strengthened community capacity. The collaboration also facilitated the emergence of five women as local innovation drivers within the community. To ensure long-term sustainability, stronger institutional support from Triple Helix actors, particularly local government, is required so that empowerment initiatives do not remain dependent on external intervention.